Aesthetic-Political Disputes around Urban Space and Memory: Locate, Displace, Replace, Overflow and Intervene Monuments - Lopez Piñeyro, Hernán; Pérez, Juan Pablo; Redruello, María Eugenia (Eikón / Imago, 2024)
Starting from the study of some particular cases of emblematic monuments, such as those of Julio Argentino Roca, Cristóbal Colón and Juana Azurduy, erected in different Argentine cities during the 20th century and the discussions they provoked, this article proposes a theoretical and situated study on monumentalization, remonumentalization and demonumentalization. At the same time, other political aesthetic practices developed by collectives of Argentine artists of the 21st century that oppose the logic of monuments and propose ways of exercising memory that assume their unstable and ephemeral character are analyzed. Finally, it is concluded that the anthropomorphic monuments of bronze or marble, beyond the figures they represent, crystallize memory but also give rise to various practices that destabilize their logics and open other vital experiences.